2012 13th International Conference on Optimization of Electrical and Electronic Equipment (OPTIM) 2012
DOI: 10.1109/optim.2012.6231897
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the winding type on the noise level of two-speed three-phase induction motors

Abstract: the purpose of this paper is to study the influence of the type of winding -double layer or single layer -to the global noise level of the machine. For this purpose, two variable speed induction motors have been studied, of the type M3AA 71 B4/8 manufactured by Electroprecizia S.A. Săcele, Romania, with Dahlander windings, star connected -for the low speed and double star connected -for the high speed. The motors are modelled from magnetic and mechanical point of view with finite element softwares. The investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They used the ANSYS program for modelling. They found that the single layer winding type results yields better than double layer winding type [12]. Chen et al carried out a new slot design to increase the induction motor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…They used the ANSYS program for modelling. They found that the single layer winding type results yields better than double layer winding type [12]. Chen et al carried out a new slot design to increase the induction motor efficiency.…”
Section: Introductionmentioning
confidence: 99%